O pensamento reflexivo crítico na formação de professores no Curso de Licenciatura em História da Universidade Federal do Amazonas - (:unkn) unknown (Universidade Federal do Amazonas, 2021)
The historian's work is commonly seen associated with the study of the past and almost disconnected from the present and, therefore, is often undervalued. However, it is important to remind the reader that, beyond the study of the past, the historian's work studies man in time and his productions, whether material or not. Such work requires a reflective capacity, however, reflection is a quality inherent to human beings, who by the simple act of thinking about their actions are already reflecting on them. However, what we intend in this work is to think about the process of training professionals in history if this training allows them not to be able to reflect, but to reflect critically. Therefore, we designed as a general objective to analyze the development of reflexive-critical thinking in the scope of the degree in History at the Federal University of Amazonas. Among the specific objectives we list: 1. Discuss the possible contributions of Paul Ricoeur to the qualification of history teachers in the 21st century; 2. Understand the fundamentals of the reflective-critical qualification of History teachers; 3. To analyze the PPC (in force in the first decade of the 21st century) of the Licentiate Degree in History at UFAM located at the Manaus Campus and its implications for the reflexive-critical qualification of History teachers. It is, therefore, a qualitative research whose method is the critical-hermeneutics in the perspective of Paul Ricoeur, having as a procedure the bibliographical and documental researches. The data obtained lead us to believe that the formation of reflexive-critical thinking is not built on the structuring bases of the PPC of the course in question.
Keywords: Professores de história - Formação; CIENCIAS HUMANAS:EDUCACAO; História; Professor Reflexivo; Pensamento Reflexivo-crítico; Formação de Professores